Metamorphosis of whitemouth croaker Micropogonias furnieri (Pisces, Sciaenidae) - Braverman, Mara Silvia (2020)
Fish metamorphosis is an important ontogenetic process with a key role on early stages survival and on successful recruitment to adult populations. The whitemouth croaker (Micropogonias furnieri) is an important commercial resource for the coastal fisheries of Argentina and Uruguay. We studied its metamorphosis, using morphometric and morphological analyses during larval development. Changes in morpho-meristic characters before and after metamorphosis were employed to determine the length interval of this transition by employing Principal Component Analysis. Individuals (n=430) from 4 to 41 mm standard length (SL) were collected in the Río de la Plata estuary (35.45º S, 56.35º W) in March, 2006. Length ranges of individual´s developmental stages were associated with the presence of key morphological characters. During early life stages, M. furnieri changes from a big-headed, larval robust shape, to a slender and more elongated body form. Most of the morphometric variables showed an inflexion point at 15.2 mm SL, with a 95% confidence interval of 14 ? 16.4 mm. The anterior part of the body grows faster during early stages, probably related to an intense feeding activity strategy. The completion of pectoral fin rays and the onset of squamation determine the beginning of metamorphosis, at 11-12 mm SL. Squamation ends at around 18 mm SL, at the same time the first barbels develop and the sagittae otolith primordium is closed. The length-at-metamorphosis for M. furnieri was established between 9 to 18 mm SL, since all developmental characters we studied highly overlapped at that interval. All those processes are indicative of the beginning of the juvenile period, which is associated to settlement and the start of a bottom-oriented life-style.